Intracellular self-assembly of Ru(bpy)32+ nanoparticles enables persistent phosphorescence imaging of tumors. Issue 28 (21st March 2018) - Li, Jindan; Hai, Zijuan; Xiao, Huiqiong; Yi, Xiaoyi; Liang, Gaolin
Abstract : The small molecular Ru(bpy)3 2+ -derivative probe1 was rationally designed for intracellular self-assembly of1-NPs for tumor imaging with persistent phosphorescence. Abstract : Nanoprobes are advantageous over small molecular probes in sensitivity but most luminescence molecules used to construct nanoprobes often suffer from an aggregation-caused quenching effect. Herein, we rationally designed a small molecular probe Cys(S t Bu)-Lys(Ru(bpy)3 2+ )-CBT (1 ) which "smartly" self-assembled into nanoparticles1-NPs inside cells with non-quenched, persistent phosphorescence. Employing this property, we successfully applied1 for long-term sensing of biothiol activity in living HepG2 cells and tumors. We envision that, by modifying the amino group with an enzyme substrate, our probe1 could be further developed for sensing intracellular enzyme activity with non-quenched, persistent phosphorescence.